Effects of Industrialization, Technology and Labor efficiency on Electricity Consumption: Panel Data Experience of Rwanda, Tanzania and Kenya. - Daniel Mburamatare, Daniel; Gboney, William K.; Hakizimana, Jean De Dieu; Mutemberezi, Fidel (International Journal of Energy Economics and Policy, 2022)
The objective of this paper is to investigate the effects of industrialization, technology and labor efficiency on electricity consumption in East African Region especially in Rwanda, Kenya and Tanzania over the period from 1990 to 2019. This study adopts a three-stage approach, we used four different panel unit root tests including Levin, Lin and Chu (LLC); Im, Pesaran, and Shin (IPS); ADF - Fisher Chi-square and PP - Fisher Chi-square. The results reveal that all variables are stationary and integrated with order one. Pedroni's cointegration tests reveals that the variables are not cointegrated while Johansen Fisher and error correction-based panel cointegration tests reveal that all variables are cointegrated with at most one cointegrating equation. The study uses Full Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) to estimate the long run relationship among the variables. We find that the increase in industrialization increases electricity consumption whiles increase in technology and enhanced labor efficiency decreases electricity consumption. The study recommends that countries need to consider the current level and the future GCF in planning of electricity supply and production to meet demand, promote efficient use of innovative technology and improve labor efficiency in the industrial sector.